Memilih dan Memanfaatkan Tipografi - Rina Kartika (Humaniora, 2015)
Typography is one of the main components of a visual communication design work as a means to convey the message to its target audiences. In delivering the information, typography stabilizes visual and verbal aspect of the overall design. The understanding of the messages (including its related aspects, such as: product knowledge, target audience’s profile, media planning, etc) is the most important thing that will help define the combination of typeface needed. This study was conducted by observation, information gathering, and typography design study of several examples. Furthermore, the understanding of typography was linked on how to choose the right typography for visual design. Result showed that the combination should have a good balance of ‘legibility’ and ‘readability’. As a conclusion, a good typography design will deliver such perception, as well as express desired impression, in a visual communication design work.